ANALISIS KESIAPAN ORANG TUA MENDAMPINGI ANAK USIA SEKOLAH DASAR DALAM PEMBELAJARAN JARAK JAUH SELAMA MASA PANDEMI COVID-19 - Zephisius Rudiyanto Eso Ntelok; Fransiska Jaiman Madu; Mariana Jediut; Marlinda Mulu (STKIP Melawi, 2021)
The aim of this study is to analyze the readiness of parents to assisted elementary school-aged children in distance learning in the 2021/2022 academic year. This study uses a qualitative approach with a descriptive method. Sample in this research were 120 parents of students who were randomly selected from 10 primary schools in the Langke Rembong district of Manggarai Regency. Data were collected by online surveys and by telephone calls. The results showed that the majority of parents were not ready to accompany their children to learn from home. This unpreparedness is caused by the difficulty of parents dividing time at home, the lack of direction received from the teacher, parents do not understand the child's subject matter, and parental ignorance of technology causes parents to tend not to be involved in children's learning activities and then hand over the responsibility to other adult family members.